2004
DOI: 10.1111/j.1600-051x.2004.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric contamination during ultrasonic scaling

Abstract: Within the restrictions of this study, only limited atmospheric microbial contamination is produced when using a piezoelectric ultrasonic scaler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 14 publications
4
76
0
7
Order By: Relevance
“…32,33 One limitation of the present study is that it presents results for a single dental procedure, prophylaxis with an ultrasonic scaler that has been shown to have a great potential for aerosol generation in the dental office. 1,2,3,4,5,39 However, other dental procedures can also generate a large amount of aerosol with infectious components launched into the dental environment, such as the air turbine handpiece, 6,7 air-water from a three-way syringe 8 and sodium bicarbonate jet. 39 Therefore, one could assume that rinsing with CPC would yield similar benefits if used before the majority of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 One limitation of the present study is that it presents results for a single dental procedure, prophylaxis with an ultrasonic scaler that has been shown to have a great potential for aerosol generation in the dental office. 1,2,3,4,5,39 However, other dental procedures can also generate a large amount of aerosol with infectious components launched into the dental environment, such as the air turbine handpiece, 6,7 air-water from a three-way syringe 8 and sodium bicarbonate jet. 39 Therefore, one could assume that rinsing with CPC would yield similar benefits if used before the majority of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies analyzed the microbial composition of dental clinics [23-29, [67][68][69][70][71][72][73][74][75][76]. The studies cumulatively identified 38 types of micro-organisms by using culture techniques (see Table 3 for complete overview of micro-organisms identified and Table 4 for study characteristics in dental setting).…”
Section: Dental Environmentmentioning
confidence: 99%
“…The ultrasonic scalers must be used with a large amount of coolant to keep the scaler tip and handle from becoming too hot. The coolant water spraying against the tip of the scaler greatly increases the aerosol volume (85, 86).…”
Section: Sonic and Ultrasonic Scalersmentioning
confidence: 99%